ANALISIS PENGARUH SUKUK WAKAF TERHADAP PEMBERDAYAAN MASYARAKAT INDONESIA - Waluyo, Waluyo; Azzahra Pradina, Arida; Amaliah, Desti; Daffa Kristantyo, Hervian (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Waqf sukuk is an innovative sharia financial instrument that integrates sukuk and waqf principles to optimize community empowerment in Indonesia. This study aims to analyze the influence of waqf sukuk on community empowerment using a literature review method from various related literature, documents, and regulations. The findings indicate that waqf sukuk, particularly through the Cash Waqf Linked Sukuk (CWLS) scheme, plays a significant role in supporting the financing of sustainable social projects in education, health, and the economy, while also expanding the benefits of waqf beyond the religious sector. The issuance of CWLS in Indonesia has involved various nazhir institutions and distribution partners that channel returns for economic empowerment programs, scholarships, health facility development, and strengthening MSMEs. However, the optimization of waqf sukuk still faces challenges such as community literacy, management trans parency, regulation, and technology utilization. Therefore, enhancing understanding, cross-sector collabo ration, and comprehensive policy support are essential to maximize the potential of waqf sukuk as an economic empowerment instrument and to achieve sustainable development goals in Indonesia.